Pemeriksaan cacing saluran pencernaan Harimau sumatra (Panthera tigris sumatrae) di Kebun Binatang Kandi Sawahlunto - Ronas Salfitra; Siagian, Tetty Barunawati (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2022)
The purpose of this study was to identify gastrointestinal worms in Sumatran tigers (Panthera tigris sumatrae) in The Taman Satwa Kandi Sawahlunto, West Sumatra. The qualitative examination was carried out on male and female tigers with native and floating methods. The results showed that both of Sumatran tigers were positive for nematode eggs, namely ascarid and trichurid worm eggs. The type of adult worm that produces eggs for ascarid worms on the Sumatran tiger is Toxocara cati while the adult worm that produces eggs of trichurid worms is Trichuris trichiura.